Kepastian Hukum Penjualan Dibawah Tangan yang Dilakukan Oleh Kurator dalam Pemberesan Budel Pailit - Dian Rizki Novita Sinaga; Yuhelson Yuhelson; Felicitas Sri Marniati (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Discussion on the legal certainty of underhand sales carried out by curators in the settlement of bankrupt estates. The method used in this research is a normative legal research type, namely library legal research or secondary data with primary, secondary and tertiary legal sources. The results of the research on the Legal Certainty of Underhand Sales Carried Out by Curators in the Settlement of Bankrupt Estates are valid and carried out with the permission of the Supervisory Judge as regulated in Article 185 paragraph 2 of the Bankruptcy Law "In the event that public sales as referred to in paragraph (1) are not achieved, underhand sales can be carried out with the permission of the Supervisory Judge. In addition, the advice expected is that curators must act with professional care to maintain independence and minimize legal risks.